2010
DOI: 10.2119/molmed.2010.00204
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stress Elicited by Bungee Jumping Suppresses Human Innate Immunity

Abstract: Although a relation between diminished human immunity and stress is well recognized both within the general public and the scientific literature, the molecular mechanisms by which stress alters immunity remain poorly understood. We explored a novel model for acute human stress involving volunteers performing a first-time bungee jump from an altitude of 60 m and exploited this model to characterize the effects of acute stress in the peripheral blood compartment. Twenty volunteers were included in the study; hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…The long‐term endurance work resulted in two major effects on the salivary protein pool in both athletes. First, the decrease of immune response proteins (Table ), reflecting the increase in cortisol to androstenedione ratio in the early stress phase, with cortisol having suppressive effects on the immune system . Second, the overrepresentation of proteins with functions in redox regulation (Table ) during the stress phase.…”
Section: Resultsmentioning
confidence: 99%
“…The long‐term endurance work resulted in two major effects on the salivary protein pool in both athletes. First, the decrease of immune response proteins (Table ), reflecting the increase in cortisol to androstenedione ratio in the early stress phase, with cortisol having suppressive effects on the immune system . Second, the overrepresentation of proteins with functions in redox regulation (Table ) during the stress phase.…”
Section: Resultsmentioning
confidence: 99%
“…Another potential pathomechanism linking the acute stress and cerebrovascular episode may be an altering of the immune system. In an experimental study of bungee jumping it has been shown that such a stressful situation significantly increases leukocyte counts, chemokine interleukin-8, proinflammatory cytokine Tumor Necrosis Factor-alpha (TNFalpha) with unaltered induction of the anti-inflammatory cytokine Il-10 [33]. On the other hand an increased level of cortisol, an immunosuppressive hormone, is observed as a response to stress [34].…”
Section: Potential Pathomechanismsmentioning
confidence: 99%
“…These activities increase state anxiety (Hare, Wetherell, & Smith, 2013), activate sympathoadrenalmedullary and hypothalamic-pituitary-adrenal stress responses (Chatterton, Vogelsong, Lu, & Hudgens, 1997). Acute experiential stress may acutely activate cellular immune parameters, for example by mobilising NK cells (Schedlowski et al, 1993); a finding that has been mirrored in numerous studies employing acute laboratory-based stressors (Segerstrom & Miller, 2004), but may also inhibit innate immune function (van Westerloo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Immune reactivity to acute experiential stress has been demonstrated in first-time skydivers (Schedlowski et al, 1993) and bungee jumpers (van Westerloo et al, 2011). These activities increase state anxiety (Hare, Wetherell, & Smith, 2013), activate sympathoadrenalmedullary and hypothalamic-pituitary-adrenal stress responses (Chatterton, Vogelsong, Lu, & Hudgens, 1997).…”
Section: Introductionmentioning
confidence: 99%